1990
DOI: 10.1152/jappl.1990.69.5.1657
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of chemical and high vascular pressure injury in isolated canine lung

Abstract: Because both chemical and mechanical insults to the lung may occur concomitantly with trauma, we hypothesized that the pressure threshold for vascular pressure-induced (mechanical) injury would be decreased after a chemical insult to the lung. Normal isolated canine lung lobes (N, n = 14) and those injured with either airway acid instillation (AAI, n = 18) or intravascular oleic acid (OA, n = 25) were exposed to short (5-min) periods of elevated venous pressure (HiPv) ranging from 19 to 130 cmH2O. Before the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Similarly, the response was attenuated in TRPV4 2/2 mice. Though there was a tendency for Ca 21 intensity to increase in these latter groups, HiPv-induced recruitment of Ca 21 entry pathways other than TRPV4 was considered unlikely, since the response to HiPv remained the same in knockout lungs pretreated with the nonspecific Ca 21 entry blocker GdCl 3 .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Similarly, the response was attenuated in TRPV4 2/2 mice. Though there was a tendency for Ca 21 intensity to increase in these latter groups, HiPv-induced recruitment of Ca 21 entry pathways other than TRPV4 was considered unlikely, since the response to HiPv remained the same in knockout lungs pretreated with the nonspecific Ca 21 entry blocker GdCl 3 .…”
Section: Resultsmentioning
confidence: 93%
“…*P , 0.05 versus BL; # P , 0.05 versus wild-type control group. when Pv exceeds approximately 30 to 50 cm H 2 O in mammalian lung (2)(3)(4)(20)(21)(22). Using vascular corrosion casting with low viscosity prepolymerized methyl methacrylate, we have shown that the alveolar septal barrier is the site of leak in the pulmonary circulation when HiPv increases permeability (23).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As shown in Fig. 1, K f,t varies as a function of body weight (BW) for mouse (11,16,32), rat (2,3,18), rabbit (1,4), dog (21,29), and sheep (8,22) as well as a predicted value for a 70-kg human. The relationship of K f,t to body mass is similar to that for alveolar (S ALV ) or pulmonary capillary (S CAP ) surface areas and pulmonary diffusion coefficient for oxygen (D L O 2 ) determined by Weibel and associates using morphometric methods (31).…”
mentioning
confidence: 95%